Teaching Project Management at a South African Tertiary Institution - Saungweme, Percy W (South African Journal of Higher Education, 2016)
The subject of project management is relatively new and has increased in stature over the years as its use expanded across disciplines from construction-based projects to initiatives that have scope, time and cost constraints. Developing effective pedagogical approaches is key to the development of the subject. This paper highlights some significant factors and suggests examples of best practice based on qualitative data collected from teaching and learning experiences gained at the University of the Western Cape in South Africa. The paper follows a reflective approach and uses multiple project cases to propose areas of focus for teaching project management using the Project Based Learning approach.